2016
DOI: 10.1016/j.celrep.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Self-Antigen-Driven Thymic B Cell Class Switching Promotes T Cell Central Tolerance

Abstract: Summary B cells are unique antigen presenting cells because their antigen presentation machinery is closely tied to the B cell receptor. Autoreactive thymic B cells can efficiently present cognate self-antigens to mediate CD4+ T cell negative selection. However, the nature of thymocyte-thymic B cell interaction, and how this interaction affects the selection of thymic B cell repertoire and in turn the T cell repertoire are not well understood. Here we demonstrate that a large percentage of thymic B cells have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 53 publications
12
63
0
3
Order By: Relevance
“…On the other hand, Thymic B-cells are preferably found in the cortico-medullary region, where they could act as antigen-presenting cells (APCs) eliminating autoreactive CD4 T cells (previously stimulated with the same type of antigen) (Perera et al 2013;Lu et al 2015;Perera et al 2016). Furthermore, studies have demonstrated that thymic B-cells promote regulatory T cells (Treg) development and proliferation (Grey et al 2014;Lu et al 2015).…”
Section: Unusual Increase Of B-cells In the Thymus Of Mice Inoculatedmentioning
confidence: 99%
“…On the other hand, Thymic B-cells are preferably found in the cortico-medullary region, where they could act as antigen-presenting cells (APCs) eliminating autoreactive CD4 T cells (previously stimulated with the same type of antigen) (Perera et al 2013;Lu et al 2015;Perera et al 2016). Furthermore, studies have demonstrated that thymic B-cells promote regulatory T cells (Treg) development and proliferation (Grey et al 2014;Lu et al 2015).…”
Section: Unusual Increase Of B-cells In the Thymus Of Mice Inoculatedmentioning
confidence: 99%
“…These physiological thymic B cells commonly show dendritic morphology and contribute to T cell tolerance . Most of them are not mature immigrants from outside the thymus but develop in situ from immature precursors . In addition, the medulla harbors desmin + , noninnervated, fetal‐type striated muscle cells called thymic myoid cells (TMCs) that express fetal and adult‐type AChRs and other striational autoantigens, including titin and, most likely, RYRs …”
Section: The Normal Thymusmentioning
confidence: 99%
“…En coopération avec les LT, les LB thymiques peuvent réaliser une commutation de classe. L'inhibition de cette commutation est à l'origine de l'émergence d'un nombre plus important de LT autoréactifs, ce qui suggère un rôle important des LB thymiques commutés dans la sélection [17]. Le répertoire de ces LB thymiques présente un biais d'utilisation en faveur du VH4 (variable heavy chain region 4), une famille de gènes impliqués dans la recombinaison V(D)J, fréquemment rencontrés dans un contexte auto-immun [5,19].…”
Section: Expression De Bcr Autoréactifsunclassified
“…En 2016, la génération d'anticorps à partir de LB naïfs thymiques, par Rother et al, a confirmé le caractère autoréactif plus important envers des antigènes protéiques, des LB thymiques par rapport à leurs équivalents de la moelle osseuse [30]. Ces LB autoréactifs peuvent capter efficacement différents autoantigènes au moyen de leur BCR et présenter des peptides dérivés de ces autoantigènes, par l'intermédiaire du CMH-II, aux thymocytes en développement [10,17,21]. L'interaction des LB autoréactifs avec les LT SP autoréactifs pourrait conduire à l'activation des LB thymiques, via l'interaction CD40-CD40L, et faciliter la commutation de classe.…”
Section: Expression De Bcr Autoréactifsunclassified
See 1 more Smart Citation